Diversidade genética do complexo de espécies de Cryptococcus gattii no estado de Mato Grosso, Brasil - Maruyama, Fernanda Harumi (2019)
Associated with high mortality, the cryptococcosis is caused by fungi of the genus Cryptococcus. Owing to its importance, this study aimed to analyze the genetic diversity of C. gattii isolates from animals, humans, and the environment in Mato Grosso State (MT), Brazil, during November 2010–December 2017. All isolates of the C. gattii species complex were subjected to molecular genotyping via Restriction Fragment Length Polymorphism (PCR–RFLP) and Multi-locus Sequence Typing (MLST). PCR–RFLP analysis revealed that 21 isolates presented the genotype VGII, which is considered the most common and virulent genotype globally among. MLST analysis revealed the presence of 14 sequence types (STs), of which 5 are considered new genotypes. Clonal Complex (CC) CC182 (n = 5; 23,80%) and CC309 (n = 3; 14,28%) were the most frequent. CC distribution in relation to origin revealed that three CCs were found in animals with a predominance of CC182 (66,66%), while nine in humans, and two CCs in the environment. Extensive genetic variability was observed among the isolates in the State of Mato Grosso. STs belonging to the already described clonal complexes (CC) indicate the global expansion and adaptation of isolates in several other countries. Therefore, detection of clonal complexes and STs already described in other regions and the occurrence of new STs in the present study help further the current understanding of the geographic dispersion and genetic origin of the C. gattii species complex.